The problem of God and sacrifice in African traditional religion - Ukpong, Justin S. (Journal of Religion in Africa, 1983)
In West African traditional religion, God is acknowledged as supreme, but often is not given sacrifice, while the minor divinities receive frequent sacrifices. In this article two current theories–the "Deus otiosus" and the mediumistic theories–which seek to explain this phenomenon are examined and rejected. An alternative explanation, based on African understanding of sacrifice as a means of entry into the divine presence, is offered. For West Africans, religious decorum forbids frequent entry into the divine presence. Hence sacrifice, a means of entry into the divine presence, is not offered frequently.
free
Keywords: Africa – Religion; Ancestors – Religious aspects; Eliade; Mircea; 1907-1986; Evans-Pritchard; E E. (Edward Evan); 1902-1973; God (African religion); God – Activity; God – Hiddenness; God – Idleness; Mediums; Sacrifice – African religion; Spirits